The subject/Culture report in the trauma of rape: the case of the Algerian girls - Houda Bouzidi (Mediterranean Journal of Clinical Psychology, 2017)
The originality of this work lies in the fact that it studied the subject within his culture, differently from many Western studies, studying especially the migrant subjects. It is there a study of indigenous psychology. However, the theoretical framework remains ethnopsychiatry. Indeed, to describe the subject/Culture report in the case of trauma, we used the method of the study of clinical cases of ten girls Algerian victims of rape. The search results well revealed, among all of the victims, a link of attachment to the culture, and that the degree of attachment varies according to the singular space that the trauma causes within each of them.